Advances in nonlinear speech processing 5th International Conference on Nonlinear Speech Processing, NOLISP 2011, Las Palmas de Gran Canaria, Spain, November 7-9, 2011. Proceedings - Travieso-González, Carlos M.; Alonso-Hernández, Jesús B. (Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the 5th International Conference on Nonlinear Speech Processing, NoLISP 2011, held in Las Palmas de Gran Canaria, Spain, in November 2011. The purpose of the workshop is to present and discuss new ideas, techniques and results related to alternative approaches in speech processing that may depart from the main stream. The 33 papers presented together with 2 keynote talks were carefully reviewed and selected for inclusion in this book. The topics of NOLISP 2011 were non-linear approximation and estimation; non-linear oscillators and predictors; higher-order statistics; independent component analysis; nearest neighbors; neural networks; decision trees; non-parametric models; dynamics of non-linear systems; fractal methods; chaos modeling; and non-linear differential equatio